Proceedings of the Twenty-third Annual Meeting of the American Association of Collegiate Schools of Business (Book). - Rickard, E. B. (The Accounting Review, 1942)
Reviews the book "Proceedings of the Twenty-Third Annual Meeting of the American Association of Collegiate Schools of Business."